AUDIT QUALITY: TREND REVIEW AND RESEARCH GAP BY USING CONTENT MINING TECHNIQUE - Fifitri Ali (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This study conducted a content mining technique to analyze the articles based on bibliographic coupling (BC) to determine the salient research subjects. These audit quality research subjects were verified with those proxies by the International Auditing and Assurance Standard Boards (IAASB) framework with a total 520 articles from 1993 to 2018 were analyzed. The result found 14 topics based on bibliographic coupling analyze. In terms of most contributing countries, USA become the most influential countries in audit quality research. Moreover, this study also identified the highly cited references and most productive authors during 1993 to 2018. The results showed that auditor characteristic (AC) was the most attractive topics in audit quality research during 25 years. The results of this study will help researchers look into their own field specialties, understand the developing trends in audit quality research, indicate researchers who have had influence in audit quality research, and determine future research subjects.